0803 Sleep Duration and Depressive Symptoms in Chinese Adolescents: a 3-wave Prospective Cohort Study. (12th April 2019) - Liu, Bao-Peng; Liu, Zhen-Zhen; Wang, Ze-Ying; An, Di; Wei, Yan-Xin; Liu, Xianchen; Jia, Cunxian
Abstract: Introduction: Little is known about the longitudinal association between sleep duration and depressive symptoms (DS) in Chinese adolescents. This study aimed to examine the prospective association between sleep duration on weekdays and weekends and the association of DS with difference in sleep duration between weekdays and weekends in a large sample of Chinese adolescents. Methods: Shandong Adolescent Behavior and Health Cohort (SABHC) is an ongoing longitudinal study in Shandong, China. A total of 6621 adolescents who participated in the baseline survey and were resurveyed 1 year or 2 years later were included in the analysis. Participants completed a self-administered questionnaire at baseline and follow-up surveys to collect information about DS, insomnia, and sleep duration on weekdays and weekends. The Center for Epidemiologic Studies Depression (CES-D) was used to assess DS. Generalized estimation equation was used to estimate the risk of DS associated with sleep duration. Non-linear trends of odds ratios of DS associated with sleep duration were described by restrictive cubic spline. Results: The mean age of the sample at baseline was 14.55 (SD=1.46) and 51.1% were males. The incidence rates of DS at 1-year and 2-year follow-ups were 3.9% and 7.3%, respectively. After adjusting for adolescent and family covariates and insomnia, short sleep duration on weekdays (<6h:OR=2.16, 95%CI: 1.65-2.81; 6h: OR=1.29, 95%CI: 1.01-1.64) and weekends (<6h: OR=2.11, 95%CI: 1.36-3.27) was significantly associated with increased risk of DS. Sleep duration >=11h on weekends was also associated with increased risk of DS (OR=1.63, 95%CI: 1.21-2.20). Sleep duration on weekends showed a U-sharp relationship with DS, with the nadir at 9.5h. Furthermore, the risk of DS began to increase if the difference in sleep duration between weekends and weekdays was >=4h. Conclusion: Our findings suggest that short sleep duration (<=6 h) on weekdays and weekends (<6 h), long sleep duration (>=11h) on weekends, and the difference in sleep duration>=4 h between weekends and weekdays are all associated with increased risk of subsequent depressive symptoms in adolescents. Support (If Any): None